Defoaming agent for industrial automobile paint and preparation method thereof

By using compounding technologies such as star-shaped block polyether-siloxane copolymer and nano-hydrophobic silica aerogel, the problems of poor defoaming effect and insufficient compatibility of existing defoamers in industrial automotive paints have been solved, achieving efficient and stable defoaming performance and paint film quality.

CN121108798APending Publication Date: 2025-12-12SHANDONG NORMAL UNIV EXPERIMENTAL PLANT CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202511528304.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-10-24
Publication Date
2025-12-12

AI Technical Summary

Technical Problem

Existing defoamers cannot simultaneously achieve high efficiency in defoaming, foam suppression, excellent compatibility, and storage stability in industrial automotive paints, leading to surface defects and storage stability issues in the paint film.

Method used

By employing a compounding technique of star-shaped block polyether-siloxane copolymer, nano-hydrophobic silica aerogel, alkylbenzene solvent, and epoxy-modified polyether siloxane, a highly efficient dynamic defoamer is formed through multi-arm synergistic interfacial interaction and nano-reinforced defoaming.

Benefits of technology

It rapidly defoams at extremely low addition levels, avoiding surface defects in the paint film and maintaining long-term defoaming performance. It is suitable for solvent-based, high-solids, and water-based industrial automotive paint systems, ensuring paint film gloss and storage stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_15
    Figure SMS_15
  • Figure QLYQS_4
    Figure QLYQS_4
  • Figure QLYQS_5
    Figure QLYQS_5
Patent Text Reader

Abstract

The invention discloses a defoaming agent for industrial automobile paint and a preparation method of the defoaming agent. The defoaming agent is prepared from the following raw materials in parts by mass: 20-40 parts of a star block polyether-siloxane copolymer; 10 to 25 parts of nano hydrophobic silicon dioxide aerogel; 30-70 parts of an alkylbenzene solvent (boiling point gt: 200 DEG C); 3 to 8 parts of epoxy group modified polyether siloxane; and 1 to 3 parts of polyether modified polydimethylsiloxane. The molecular weight range of the star block polyether-siloxane copolymer can effectively balance the defoaming property and compatibility, the siloxane chain segment of the star block polyether-siloxane copolymer destroys the elasticity of a foam film, and the siloxane chain segment cooperates with alkylbenzene to reduce local surface tension and accelerate foam rupture. The polyether chain segment and the siloxane chain segment have a synergistic effect, and the polyether chain segment adjusts hydrophilicity to adapt to different environments.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the field of high polymer materials and coating additives, in particular to a defoaming agent and a preparation method thereof, and more particularly to a high-efficiency and high-compatibility defoaming agent for industrial automobile paint. BACKGROUND

[0002] The information disclosed in this Background section is for the purpose of generally presenting the context of the application. The information disclosed in this Background section is not to be taken as an acknowledgement or any form of suggestion that this information forms prior art that is already known to a person skilled in the art.

[0003] Industrial automobile paint is one of the highest-end application fields of the coating industry, and has almost perfect requirements for the appearance, mechanical properties and weather resistance of the final coating film. Any minor surface defects, such as shrinkage holes, pinholes, fish eyes or orange peel, are unacceptable. During the production (high-speed dispersion), application (high-pressure spraying) and curing process of automobile paint, micro-bubbles and macro-bubbles are easily introduced and generated. The role of the defoaming agent is to quickly and effectively eliminate these bubbles under the premise of ensuring the ultimate appearance of the paint film.

[0004] At present, the defoaming agents for industrial automobile paint applications in the industry mainly include the following types: (1) traditional polyether-modified silicone defoaming agents: this type of product improves the compatibility with polar coating systems by grafting polyether segments on the polydimethylsiloxane backbone. They balance the defoaming property and compatibility to some extent, and constitute the mainstream choice in the current market. However, they have inherent defects: the hydrophilicity of the polyether segment may lead to a decrease in the water resistance of the paint film in high-temperature and high-humidity environments; and there is still a risk of causing micro-shrinkage holes, especially in clear paint systems. (2) Hydrophobic particle enhanced silicone defoaming agents: to improve the bubble breaking efficiency, hydrophobic particles such as fumed silica are often added to silicone defoaming agents as core carriers. The particles can pierce the bubble film, significantly improving the defoaming performance. However, the new problem brought about is: the dispersion stability of the particles is a great challenge, and they are prone to sedimentation and agglomeration, resulting in poor storage stability of the product and decay of the defoaming performance over time; more seriously, the poorly dispersed particles themselves can become defects on the surface of the paint film, causing visible defects. (3) Non-silicone defoaming agents (acrylic polymers, acetylenic diols, etc.): the advantage of this type of defoaming agent is excellent compatibility with the system, and it almost never causes shrinkage holes. However, its biggest shortcoming is the generally insufficient defoaming and especially bubble suppressing efficiency, making it difficult to deal with the large amount of stable micro-bubbles generated during the application of automobile paint, and it can usually only be used as an auxiliary defoaming agent, and cannot undertake the core defoaming task alone.

[0005] With the tightening of environmental regulations, high solid coatings and waterborne coatings are increasingly widely used in the field of industrial vehicles. These two systems usually contain more surface active substances and higher viscosity, making the foam more stable and more difficult to eliminate. At the same time, the high polarity environment of waterborne system puts unprecedented high requirements on the compatibility and stability of defoamer. Many existing defoamers suitable for solvent-based systems fail, separate or lose effectiveness in waterborne systems.

[0006] In summary, the defoamers for industrial vehicle paint in the prior art have the following core contradictions and defects: It is impossible to simultaneously consider "extreme defoaming" and "extreme compatibility", and the contradiction between high-efficiency defoaming and avoiding shrinkage / hole defects is amplified to the extreme in high-end vehicle paint. The universality and effectiveness of existing defoamers in new vehicle paint systems such as high solid and waterborne are insufficient, affecting the gloss, re-coatability and long-term storage stability of the paint film. SUMMARY

[0007] The primary object of the present application is to overcome the above-mentioned defects of the prior art and provide a new defoamer specifically for industrial vehicle paint, which meets the requirements of high-efficiency defoaming, strong foam suppression, excellent compatibility and storage stability.

[0008] Specifically, the present application aims to solve the following technical problems: to provide a defoamer for industrial vehicle paint, which can quickly break the foam at a very low addition amount (usually 0.1%-0.5%) and completely avoid inducing shrinkage, fisheye and other defects on the surface of the paint film, ensuring the perfect appearance of the vehicle paint film. It has good compatibility with solvent-based, high solid and waterborne industrial vehicle paint systems, and has wide system applicability. It is stable in nature and not prone to separation and sedimentation, and can maintain defoaming efficiency for a long time. The process is simple and easy to industrialize.

[0009] The technical solution adopted by the present application is as follows: In the first aspect of the present application, a defoamer for industrial vehicle paint and a preparation method thereof are provided, which is made of the following mass parts of raw materials: 20-40 parts of star-shaped block polyether-siloxane copolymer; 10-25 parts of nano-hydrophobic silica aerogel; 30-70 parts of alkylbenzene solvent (boiling point > 200°C); 3-8 parts of epoxy-modified polyether siloxane; 1-3 parts of polyether-modified polydimethylsiloxane.

[0010] In one or some embodiments of the present application, the star-shaped block polyether-siloxane copolymer has the following general structure: The number average molecular weight of the copolymer is 5000-50000 g / mol, which has a star structure with a silsesquioxane core and n (n≥3) polyether arms connected to the core, and the structure of the polyether arm (block copolymer) is or wherein x and y are the polymerization degrees of PO and EO, respectively, and the ratio range is 1:0.5 to 1:2; R is a C2-C6 alkylene linking group, for example, (ethylene), (propylene), (isopropylene), (butylene); and the end of each arm of the star-shaped copolymer is connected to at least one polyether segment.

[0011] Further, n≤8.

[0012] The star-shaped block polyether-siloxane copolymer adopted in the present application has a three-dimensional structure with a PDMS core and multiple PEO-PPO arms, high interface coverage, star-shaped topology enhancement, and ultra-fast interface spreading. The star-shaped block polyether-siloxane copolymer has a star-shaped topology effect and multiple arms for synergistic adsorption. The 4-8 PEO-PPO arms radiate from the PDMS core in a radial manner, which can simultaneously anchor multiple foam films and significantly improve the interface coverage. The multiple arm structure of the star-shaped polymer prevents agglomeration and maintains nanodispersion. The particles form an "armor layer" with the star-shaped copolymer at the interface, which has both mechanical strength and elasticity.

[0013] In one or some embodiments of the present application, the surface of the nanohydrophobic silica aerogel is modified by a silane coupling agent, the specific surface area is 500-1000 m² / g, and the pore size distribution is 2-50 nm.

[0014] The nanohydrophobic silica aerogel adopted in the present application has a mesoporous structure, ultra-high specific surface area, superhydrophobicity, and a nanoscale sharp edge that physically pierces the foam film, adsorbs surfactants, inhibits foam regeneration, and significantly improves the defoaming efficiency and durability.

[0015] In one or some embodiments of the present application, the alkylbenzene solvent is a C10-C14 linear alkylbenzene with a substitution degree of 1 or 2, and when the substitution degree is 2, the alkyl substituent is located at the para or ortho position of the benzene ring. The boiling point of the alkylbenzene solvent is 200℃-340℃. The key point of selecting the alkylbenzene solvent of the present application is that the boiling point is greater than 200℃, not the exact composition thereof. The alkylbenzene solvent can be a single solvent or a mixed solvent, for example, it can be a single solvent-C12 linear alkylbenzene, also known as 1-phenyl dodecane.

[0016] The alkyl benzene solvent adopted in the present application has excellent siloxane compatibility, regulates the molecular conformation of star-shaped copolymer, promotes the dispersion of nanometer particles, and prevents agglomeration.

[0017] In the alkyl benzene solvent, the star-shaped copolymer presents a "shrinkage-stretching" dynamic balance, enhances hydrophobicity, and promotes the spreading of PDMS to break bubbles.

[0018] In one or some embodiments of the present application, the emulsifier is selected to be an epoxy-modified polyether siloxane, the molecular weight of which is 1000-5000 g / mol, the siloxane chain length is 10-30 Si atoms, and both the epoxy group and the polyether are linked to the siloxane main chain as side chains. The epoxy value of the emulsifier is 0.02-0.10 mol / 100 g based on the total weight of the emulsifier, and the polyether segment is a block copolymer of ethylene oxide (EO) and propylene oxide (PO), wherein the mass ratio of EO / PO is 2:1.

[0019] The synergistic defoaming and bubble breaking mechanism is as follows: the star-shaped block polyether-siloxane copolymer dominates the primary defoaming. The PEO arm quickly adsorbs the liquid film of the foam, reducing the surface tension. The PDMS core spreads on the liquid film in a "starburst" manner due to the ultra-low surface tension, forming multiple weak areas. The nanometer hydrophobic silica aerogel enhances the secondary defoaming, the particles wedge into the liquid film, and the sharp edges split the liquid film. The alkyl benzene solvent adjusts the conformation relaxation time of the star-shaped copolymer, and the present application selects a low-viscosity alkyl benzene to respond faster to the breaking of the foam.

[0020] In one or some embodiments of the present application, the polyether-modified polydimethylsiloxane has a molecular weight of 2000-5000 g / mol and comprises: a polyether segment, wherein the polyether segment is a copolymer of ethylene oxide (EO) and propylene oxide (PO), and the mass ratio of EO to PO is 1:1 to 3:1. This substance has the effects of reducing the surface tension of the system, improving the wetting and leveling of the substrate, etc.

[0021] In a second aspect of the present application, a defoaming agent for the industrial automobile paint and a preparation method thereof are provided, the method comprising the following steps: (1) In a reaction kettle, star-shaped block polyether-siloxane copolymer and alkyl benzene solvent are added, stirred, and heated to 85-95°C to uniformly mix the materials.

[0022] (2) The temperature is maintained, and nanometer hydrophobic silica aerogel is slowly added. After the addition is completed, the temperature is maintained and high-speed shearing stirring is continuously performed for 2-4 hours until the system presents a uniform paste, and no obvious silica aggregates are observed under a microscope.

[0023] (3) The paste obtained in step (2) is cooled to below 50℃, the remaining epoxy-modified polyether siloxane and polyether-modified polydimethylsiloxane are added, and the stirring is continued for 1-2 hours to fully dilute and mix evenly.

[0024] (4) The material is filtered using a filter screen to obtain a light yellow to amber liquid with a clear to slightly turbid appearance, which is the defoaming agent product of the present application.

[0025] Compared with the related art known to the present inventors, one of the technical solutions of the present application has the following beneficial effects: Through molecular design and compounding technology, the defoaming agent can perceive the physical and chemical environment it is in and dynamically adjust its existing state and action mode, thereby maintaining high-efficiency, stable and safe defoaming and foam suppression performance in the entire process of paint production. It is suitable for use in the pre-stage, grinding and dispersion stage, paint mixing stage and application stage of paint production, i.e., a new type of defoaming agent that is universal in all stages of production.

[0026] The star-shaped block polyether-siloxane copolymer and the nano-hydrophobic silica aerogel realize high-efficiency dynamic defoaming through multi-arm synergistic interfacial action and nano-enhanced bubble breaking.

[0027] The star-shaped block polyether-siloxane copolymer of the present application has a molecular weight range that can effectively balance defoaming and compatibility. The star-shaped block structure: multiple polyether-siloxane segments extend radially from the center core to form a three-dimensional spatial structure, enhancing surface spreading ability and permeability and rapidly destroying the foam film. The siloxane segment of the star-shaped block polyether-siloxane copolymer destroys the elasticity of the foam film and cooperates with the alkylbenzene to reduce the local surface tension, accelerating the rupture of the foam. The synergistic effect of the polyether segment and the siloxane segment: the polyether segment adjusts the hydrophilicity and adapts to different temperatures. High-efficiency dispersibility: the star-shaped structure improves compatibility in the system, avoiding shrinkage holes or fish eyes. Long-lasting foam suppression: the block design delays molecular migration, extending the action time.

[0028] The defoaming agent for industrial automobile paint provided by the present application does not affect the gloss of the coating, with a difference of <5% in 60° gloss meter testing; and has high thermal storage stability, with no delamination after 50℃ / 14 days. DETAILED DESCRIPTION

[0029] It should be noted that the following detailed description is exemplary and is intended to provide further explanation of the present application. Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which the present application belongs.

[0030] It is to be understood that the terminology used herein is for the purpose of describing particular embodiments only and is not intended to be limiting of example embodiments in accordance with the present application. As used herein, the singular forms "a", "an" and "the" are intended to include the plural forms as well, unless the context clearly indicates otherwise. It will be further understood that the terms "comprises" and / or "comprising," when used in this specification, specify the presence of stated features, steps, operations, elements, and / or components, but do not preclude the presence or addition of one or more other features, steps, operations, elements, components, and / or groups thereof.

[0031] In order to enable persons skilled in the art to more clearly understand the technical solutions of the present application, the technical solutions of the present application will be described in detail below in combination with specific examples.

[0032] Example 1 A defoamer for industrial automobile paint, which is made of the following raw materials by mass fraction: 20 parts of star-shaped block polyether-siloxane copolymer, 12 parts of nano-hydrophobic silica aerogel, 50 parts of alkylbenzene solvent, 8 parts of epoxy-modified polyether siloxane, 2 parts of polyether-modified polydimethylsiloxane.

[0033] The star-shaped block polyether-siloxane copolymer has a siloxane core with a number of arms n = 4, a linking group R is , the mass ratio of polyether segment to siloxane segment is 1:1, the polyether segment is a copolymer of propylene oxide (PO) units and ethylene oxide (EO) units, the ratio of the number of PO units to the number of EO units (x:y) is 1:1; the copolymer is a block copolymer with a number average molecular weight of 18000 g / mol. The star-shaped block polyether-siloxane copolymer is commercially available, for example, from Guangzhou Haoyi New Material Technology Co., Ltd., with the item number TEGO® Glide 450.

[0034] The nano-hydrophobic silica aerogel has the following performance parameters: its surface is hydrophobically treated with a silane coupling agent, the specific surface area is 600 - 800 m² / g, and the pore size distribution is 2-50 nm. The nano-hydrophobic silica aerogel is commercially available, for example, from Cabot Chemical (Shanghai) Co., Ltd., with the item number P300.

[0035] The alkylbenzene solvent is C12 linear alkylbenzene, and the solvent boiling point is 280-310°C. The alkylbenzene solvent is commercially available, for example, from Fushun Petrochemical Company of China Petroleum.

[0036] The epoxy-modified polyether siloxane has a molecular weight of 1000-3000 g / mol, a siloxane chain length of 5 to 15 Si atoms, and both epoxy groups and polyether groups are linked to the siloxane backbone as side chains. The epoxy value of the epoxy-modified polyether siloxane is 0.03 to 0.10 mol / 100 g based on the total weight of the emulsifier, and the polyether segment is a block copolymer of ethylene oxide (EO) and propylene oxide (PO) with a mass ratio of EO / PO of 70:30 to 60:40. The epoxy-modified polyether siloxane is commercially available, for example, from Momentive Performance Materials (Nantong) Co., Ltd., with the product code L-6900.

[0037] The polyether-modified polydimethylsiloxane has a molecular weight of 2000-5000 g / mol; and a polyether segment: the polyether segment is a block copolymer of ethylene oxide (EO) and propylene oxide (PO) with a mass ratio of EO to PO of 1:1. The polyether-modified polydimethylsiloxane is commercially available, for example, from BYK-Chemie (Shanghai) Co., Ltd., with the product code BYK-3455.

[0038] The method for preparing the defoamer for industrial automotive paint comprises the following steps: (1) In a reaction kettle, add star-shaped block polyether-siloxane copolymer, alkylbenzene solvent, stir and heat to 90°C, and mix the materials uniformly.

[0039] (2) Keep the temperature, slowly add nano-hydrophobic silica aerogel, after adding, keep warm and continue to stir at high speed for 3 hours, until the system is a uniform paste, and there are no obvious silica aggregates under a microscope.

[0040] (3) Cool the paste obtained in step (2) to below 50°C, add the remaining epoxy-modified polyether siloxane and polyether-modified polydimethylsiloxane, and continue to stir for 2 hours to fully dilute and mix uniformly.

[0041] (4) Filter the material using a filter screen to obtain a light yellow to amber liquid with a clear to slightly turbid appearance, which is the defoamer product.

[0042] Example 2 A defoamer for industrial automotive paint is prepared from the following raw materials in parts by mass: 40 parts of star-shaped block polyether-siloxane copolymer, 15 parts of nano-hydrophobic silica aerogel, 50 parts of alkylbenzene solvent, 5 parts of epoxy-modified polyether siloxane, and 1 part of polyether-modified polydimethylsiloxane.

[0043] The star-shaped block polyether-siloxane copolymer has a siloxane core with a number of arms n = 4, and the linking group R is , the mass ratio of the polyether segment to the siloxane segment is 1 : 1, the polyether segment is a copolymer of propylene oxide (PO) units and ethylene oxide (EO) units, the ratio of the number of PO units to the number of EO units (x:y) is 1 : 1; the copolymer is a block copolymer, and the number average molecular weight is 18000 g / mol. The star-shaped block polyether-siloxane copolymer is commercially available, for example, from Guangzhou Haoyi New Material Technology Co., Ltd., with the product number of Yingchuang TEGO® Glide 450.

[0044] The nano-hydrophobic silica aerogel has the following performance parameters: the surface thereof is hydrophobically treated by a silane coupling agent, the specific surface area is 600-800 m² / g, and the pore size distribution is 2-50 nm. The nano-hydrophobic silica aerogel is commercially available, for example, from Cabot Chemical (Shanghai) Co., Ltd., with the product number of P300.

[0045] The alkylbenzene solvent comprises C10-C14 linear alkylbenzene, the solvent boiling point of which is 300-330°C, wherein the alkyl substituent is located at the ortho position of the benzene ring, and the degree of substitution of the alkyl group on the benzene ring is 2. The alkylbenzene solvent is commercially available, for example, from Fushun Petrochemical Company of China Petroleum.

[0046] The epoxy-modified polyether siloxane has a molecular weight of 3000-5000 g / mol, a siloxane chain length of 20 to 30 Si atoms, and both epoxy groups and polyether groups are linked as side chains on the siloxane main chain. The epoxy value thereof is 0.02 to 0.04 mol / 100 g based on the total weight of the emulsifier, and the polyether segment is a block copolymer of ethylene oxide (EO) and propylene oxide (PO), wherein the mass ratio of EO / PO is 70:30-80:20. The epoxy-modified polyether siloxane is commercially available, for example, from Momentive Performance Materials (Nantong) Co., Ltd., with the product number of L-7001.

[0047] The polyether-modified polydimethylsiloxane has a molecular weight of 2000-5000 g / mol; and a polyether segment: the polyether segment is a block copolymer of ethylene oxide (EO) and propylene oxide (PO), wherein the mass ratio of EO to PO is 1:1. The polyether-modified polydimethylsiloxane is commercially available, for example, from BYK-Chemie (Tongling) Co., Ltd. Shanghai, with the product number of BYK-3455.

[0048] The preparation method is the same as that in Example 1.

[0049] Example 3 A defoaming agent for industrial automobile paint is prepared from the following raw materials in parts by mass: 40 parts of star-shaped block polyether-siloxane copolymer, 20 parts of nano-hydrophobic silica aerogel, 60 parts of alkylbenzene solvent, 8 parts of epoxy-modified polyether siloxane, 1 part of polyether-modified polydimethylsiloxane.

[0050] The star-shaped block polyether-siloxane copolymer has a siloxane core with a number of arms n = 4, a linking group R is , a mass ratio of polyether segment to siloxane segment of 1:1, the polyether segment is a copolymer of propylene oxide (PO) units and ethylene oxide (EO) units, a ratio (x:y) of the number of PO units to the number of EO units is 1:1; the copolymer is a block copolymer with a number average molecular weight of 18000 g / mol. The star-shaped block polyether-siloxane copolymer is commercially available, for example, from Guangzhou Haoyi New Material Technology Co., Ltd., with the item number TEGO® Glide 450.

[0051] The nano-hydrophobic silica aerogel has the following performance parameters: its surface is hydrophobically treated with a silane coupling agent, and the specific surface area is 600 - 800 m² / g, and the pore size distribution is 2-50 nm. The nano-hydrophobic silica aerogel is commercially available, for example, from Cabot Chemical (Shanghai) Co., Ltd., with the item number P300.

[0052] The alkylbenzene solvent comprises C10-C14 linear alkylbenzene, and the solvent boiling point is 300-330℃, wherein the alkyl substituent is located at the ortho position of the benzene ring, and the degree of substitution of the alkyl group on the benzene ring is 2. The alkylbenzene solvent is commercially available, for example, from Fushun Petrochemical Company of China Petroleum.

[0053] The epoxy-modified polyether siloxane has a molecular weight of 1000-3000 g / mol, a siloxane chain length of 5 to 15 Si atoms, and both epoxy and polyether are linked as side chains on the siloxane backbone. The epoxy value is 0.03 to 0.10 mol / 100 g based on the total weight of the emulsifier, and the polyether segment is a block copolymer of ethylene oxide (EO) and propylene oxide (PO) with a mass ratio of EO / PO of 70:30 to 60:40. The epoxy-modified polyether siloxane is commercially available, for example, from Momentive Performance Materials (Nantong) Co., Ltd., with the item number L-6900.

[0054] The polyether-modified polydimethylsiloxane has a molecular weight of 2000 - 5000 g / mol; polyether segment: the polyether segment is a block copolymer of ethylene oxide (EO) and propylene oxide (PO) with a mass ratio of EO to PO of 1:1. The polyether-modified polydimethylsiloxane is commercially available, for example, from BYK-Chemical (Tongling) Co., Ltd. Shanghai, with the item number BYK-3455.

[0055] The preparation method is the same as that of Example 1.

[0056] Comparative Example 1 The difference from Example 1 is that the component adjustment: the star-shaped block polyether-siloxane copolymer is replaced with an equal amount of linear polyether-siloxane copolymer (similar molecular weight, but no star structure, arm number n = 1), and other components and proportions remain unchanged.

[0057] Compared with Example 1, the defoaming efficiency of the linear polyether-siloxane copolymer is lower, indicating that the star structure in Example 1 can enhance the interfacial adsorption capacity due to the multi-arm topology.

[0058] Comparative Example 2 The difference from Example 1 is that the component adjustment: the nano-hydrophobic silica aerogel is replaced with an equal amount of ordinary hydrophobic fumed silica (specific surface area 200 m² / g, not treated by aerogel), and other components and proportions remain unchanged.

[0059] Compared with Example 1, the ordinary silica reduces the defoaming durability due to the low pore volume, while the high specific surface area (500-1000 m² / g) and porous structure (2-50 nm pore size) of the nano-hydrophobic silica aerogel promote the rupture of the foam.

[0060] Comparative Example 3 The difference from Example 1 is that the component adjustment: the star-shaped block copolymer with PO:EO = 1:3 is used (which exceeds the range of 1:0.5~1:2 of the present application), and other components and proportions remain unchanged.

[0061] Compared with Example 1, the excessive EO ratio leads to the defoaming agent being dissolved in the system and losing effectiveness.

[0062] Comparative Example 4 The difference from Example 1 is that the component adjustment: the high-boiling alkylbenzene solvent (boiling point > 200℃) is replaced with xylene (boiling point 140℃), and other components and proportions remain unchanged.

[0063] Compared with Example 1, the low-boiling solvent volatilizes during high-temperature curing of the coating, resulting in migration or failure of the defoaming agent.

[0064] Comparative Example 5 The difference from Example 1 is that the component adjustment: the epoxy-modified polyether siloxane is replaced with a conventional polydimethylsiloxane emulsifier (without epoxy groups). Other steps and methods are the same as those of Example 1.

[0065] Compared with Example 1, the conventional siloxane emulsifier causes the defoaming agent to agglomerate due to poor compatibility, resulting in poor defoaming effect.

[0066] Comparative Example 6 The difference compared to Example 1 is that the antifoam agent is made from the following parts by mass of raw materials: 45 parts of star block polyether-siloxane copolymer; 10 parts of nano-hydrophobic silica aerogel; 30 parts of alkylbenzene solvent; 5 parts of epoxy-modified polyether siloxane; 2 parts of polyether-modified polydimethylsiloxane. Other steps and methods are the same as Example 1.

[0067] Compared to Example 1, the antifoaming efficiency is significantly reduced due to the component ratio exceeding the preferred range of the present application.

[0068] Application Example I. Coating system and test method 1. Select the most challenging high gloss varnish.

[0069] Base paint formula example (high gloss acrylic polyurethane topcoat): Hydroxyl acrylic resin: 60-70 parts; Butyl acetate: 10-15 parts; Leveling agent: 0.2-0.5 parts; Dispersant: 0.3-0.8 parts; Curing agent (isocyanate): added before spraying in the ratio of NCO / OH = 1.1:1.

[0070] Test method a. Foam suppression test - refer to ASTM D3519-88 (2018) "Foam Suppression Test for Coatings Agitation" Method: Accurately weigh 100 g of base paint into a 250 mL metal can. Add the specified amount (0.3%) of the antifoam agent to be tested. Use a high-speed disperser to accurately stir for 2 minutes under specific conditions (2500 ± 500 rpm, fixed depth). After stirring, immediately pour all the paint into a 250 mL graduated cylinder.

[0071] Evaluation index: Immediately record the initial foam height (H0, unit: mL).

[0072] After standing for a specified time (5 minutes), record the residual foam height (Ht).

[0073] b. Compatibility / film appearance: Method: Spray the paint solution with added antifoam agent on a glass plate, flash dry and bake according to the specified conditions. Evaluate by visual observation and instrument measurement: Shrinkage, fish eyes: presence or absence and quantity.

[0074] Gloss: measured using a 60° gloss meter. The smaller the gloss loss compared to the blank sample (without any antifoam agent), the better.

[0075] Haze: using a 20° gloss meter. High gloss paint films require very low haze values.

[0076] c. Long term stability (storage stability): Method: The paint with added defoamer is stored in a sealed oven at 50°C (accelerated aging) or at room temperature for several weeks. Periodically, it is removed, observed for delamination, sedimentation, caking, and the tests a and b are repeated to check for defoaming performance decay.

[0077] II. Performance testing and results

[0078] In all tests, the amount of defoamer added to the paint was 0.3%.

[0079] From the above table, it can be seen that the defoamers in Examples 1-3 performed best: excellent foam suppression and break rate, exhibiting fast and comprehensive defoaming ability. The paint film appearance had no shrinkage and fisheyes, indicating that they were highly compatible with the system and were high-performance and safe choices.

[0080] The defoaming ability and foam suppression ability of the defoamers in Comparative Examples 1-6 were weak, and they had poor compatibility (resulting in shrinkage) and generally performed poorly.

[0081] The above examples are preferred embodiments of the present application, but the embodiments of the present application are not limited by the above examples, and any changes, modifications, substitutions, combinations, simplifications made without departing from the spirit and principles of the present application are equivalent replacement methods and are included in the protection scope of the present application.

Claims

1. A defoamer for use in industrial automotive paints, characterized in that, This defoamer is made from the following raw materials in parts by weight: 20-40 parts of star-shaped block polyether-siloxane copolymer; 10-25 parts of nano-hydrophobic silica aerogel; 30-70 parts of alkylbenzene solvent with a boiling point greater than 200℃; 3-8 parts epoxy-modified polyether siloxane; 1-3 parts of polyether-modified polydimethylsiloxane.

2. The defoamer for industrial automotive paint as described in claim 1, characterized in that, The star-shaped block polyether-siloxane copolymer has a number-average molecular weight of 5000-50000 g / mol and a star-shaped structure with a silsesquioxane core connecting n (n≥3) polyether arms. The structure of the polyether arms is as follows: or Where x and y are the degrees of polymerization of PO and EO, respectively, and their ratio ranges from 1:0.5 to 1:2; R is a C2-C6 alkylene linker, for example, (Ethylene), (Propylene), (Isopropylidene) (Butylene); each arm of the star copolymer is connected to at least one of the polyether segments.

3. The defoamer for industrial automotive paint as described in claim 2, characterized in that, n≤8。 4. The defoamer for industrial automotive paint as described in claim 1, characterized in that, The nano-hydrophobic silica aerogel has a surface modified with a silane coupling agent, a specific surface area of ​​500-1000 m² / g, and a pore size distribution of 2-50 nm.

5. The defoamer for industrial automotive paint as described in claim 1, characterized in that, The alkylbenzene solvent is a C10-C14 straight-chain alkylbenzene with a degree of substitution of 1 or 2. When the degree of substitution is 2, the alkyl substituent is located at the para or ortho position of the benzene ring. The boiling point of the alkylbenzene solvent is 200℃ - 340℃.

6. The defoamer for industrial automotive paint as described in claim 1, characterized in that, The epoxy-modified polyether siloxane has a molecular weight of 1000-5000 g / mol and a siloxane chain length of 10-30 Si atoms. Both the epoxy group and the polyether are attached as side links to the siloxane main chain. Based on the total weight of the emulsifier, its epoxy value is 0.02-0.10 mol / 100g. The polyether segment is a block copolymer of ethylene oxide (EO) and propylene oxide (PO), wherein the mass ratio of EO / PO is 2:

1.

7. The defoamer for industrial automotive paint as described in claim 1, characterized in that, The polyether-modified polydimethylsiloxane has a molecular weight of 2000-5000 g / mol, and the polyether segment is a copolymer of ethylene oxide (EO) and propylene oxide (PO), wherein the mass ratio of EO to PO is 1:1 to 3:

1.

8. The method for preparing the defoamer for industrial automotive paint according to any one of claims 1 to 7, characterized in that, The method includes the following steps: (1) Add star-shaped block polyether-siloxane copolymer and alkylbenzene solvent to the reactor, stir and heat to 85-95℃ to make the materials mix evenly; (2) Keep the temperature and slowly add the nano-hydrophobic silica aerogel. After the addition is complete, keep the temperature and continue to shear and stir at high speed for 2-4 hours until the system is a uniform paste and no obvious silica aggregates are observed under a microscope. (3) Cool the paste obtained in step (2) to below 50°C, add the remaining epoxy-modified polyether siloxane and polyether-modified polydimethylsiloxane, and stir continuously for 1-2 hours to make it fully diluted and mixed evenly. (4) The material is filtered using a filter screen. The light yellow to amber liquid has a clear to slightly turbid appearance and is used as a defoamer for industrial automotive paint.

Citation Information

Cited By

  • Preparation process of siloxane-polyether copolymer modified coking defoaming agent

    CN121648614A